Development of ergotherapy as a method of treatment and rehabilitation in the inclusive environment of modern Ukraine social, philosophical and legal aspects - Anishchenko, M. A.; Zubov, V.; Serhatyi, M.; Serhata, N.; Bondarenko, O.; Аніщенко, Михайло Анатолійович (My University, 2021)
The article examines the socio-philosophical aspect of the development of ergotherapy as a method of treatment and rehabilitation in an inclusive environment. The legal features of the introduction, functioning and further development of ergotherapy in Ukraine are considered. The paper examines the features of cooperation between Ukrainian state bodies and the professional ergotherapeutic environment. The article examines the philosophical ideas of Plato about the role of manual labor in ancient law and its role in the formation of personality. The relationship between physical activity and health preservation in the works of Avicenna has been clarified. The philosophical developments of E. Kant in the field of overcoming pain are investigated. The ideas of the primacy of the natural essence of health by Francis Bacon are investigated. The article examines the positivity from attempts to philosophically substantiate new ergotherapeutic concepts developed by Ukrainian scientists, in particular, the concept of Natural Therapy as a combination of animal therapy, agrotherapy and garden therapy into a single integral rehabilitation concept for various nosologies, developed by a team of scientists. The article analyzes the shortcomings of the Ukrainian legislation in the field of regulatory support of ergotherapy and offers own proposals for its improvement, which will be implemented by improving the existing legislation in the field of rehabilitation activities and introducing new laws in the field of social rehabilitation and a separate law on the implementation of ergotherapeutic activities.
Keywords: medical rehabilitation; physical rehabilitation; ergotherapy; philosophical concept of ergotherapy; legal regulation of ergotherapeutic technologies in Ukraine